Recent developments in phase‐change memory. Issue 4 (4th July 2022) - Ehrmann, Andrea; Blachowicz, Tomasz; Ehrmann, Guido; Grethe, Thomas
Abstract: Phase‐change memory (PCM) belongs to the nonvolatile solid‐state memory techniques. Usually, a chalcogenide is sandwiched between two conductive electrodes and data are stored by setting each cell to a low‐resistance (crystalline) or a high‐resistance (amorphous) state. Switching between these states is relatively fast, which makes phase‐change random access memories (PCRAMs) highly interesting for nonvolatile memories. Multilevel cells, which can store more than 1 bit per cell, and multilayer high‐density memory arrays have also been reported as advantages of PCRAM. Writing currents and data retention, on the other hand, still show potential for optimization. This review gives an overview of the most recent developments in new material compositions and material‐related optimization of PCM in comparison with already produced PCM. Abstract : Phase‐change memory (PCM) belongs to the nonvolatile solid‐state memory techniques. Data are stored by setting each cell to a low‐resistance (crystalline) or a high‐resistance (amorphous) state. Although fast switching and multilevel data storage are advantageous, writing currents and data retention still show potential for optimization. This review gives an overview of the most recent developments in new material compositions and material‐related optimization of PCM in comparison with already produced PCM.